Hubungan Pola Asuh Orang Tua Dengan Masalah Mental Emosional Remaja - Yeni Devita (Universitas Batanghari Jambi, 2020)
The results of WHO research and Basic Health Research in 2013 found that adolescents experience mental emotional problems. One of the factors causing adolescent mental emotional problems is parenting. This study aims to determine the relationship of parenting parents with adolescent mental emotional problems. Descriptive analytic research design, cross sectional approach, a sample of 266 adolescents. The results showed the average authoritarian parenting was 27.31, democratic parenting 30.30, and permissive parenting 29.05. The dominant parenting pattern is democratic parenting. Adolescent mental emotional problems are included in the borderline category with an average score of 18-19. The average age of adolescents is 16-17 years. The sex of adolescents is 54.9% female. Teen education 82% higher education. Parents' occupations 61.7% formal employment. Parents' education is 63.5% highly educated. The socioeconomic level is 58.3% low. There is a relationship between authoritarian parenting, democratic, permissive, adolescent age, parental work, parental education, and socioeconomic level with adolescent mental emotional problems. The most influential variables with mental emotional mental adolescent problems are permissive parenting. Suggestions for science psychiatric nursing further develops education related to parental care that can be applied to prevent adolescent emotional emotional problems.